The Piezo-Hyperthermophilic Archaeon Thermococcus piezophilus Regulates Its Energy Efficiency System to Cope With Large Hydrostatic Pressure Variations - Moalic, Yann; Hartunians, Jordan; Dalmasso, Cécile; Courtine, Damien; Georges, Myriam; Oger, Philippe; Shao, Zongze; Jebbar, Mohamed; Alain, Karine (Frontiers in Microbiology, 2021)
Deep-sea ecosystems share a common physical parameter, namely high hydrostatic pressure (HHP). Some of the microorganisms isolated at great depths have a high physiological plasticity to face pressure variations. The adaptive strategies by which deep-sea microorganisms cope with HHP variations remain to be elucidated, especially considering the extent of their biotopes on Earth. Herein, we investigated the gene expression patterns of Thermococcus piezophilus, a piezohyperthermophilic archaeon isolated from the deepest hydrothermal vent known to date, under sub-optimal, optimal and supra-optimal pressures (0.1, 50 and 90 MPa, respectively). At stressful pressures (sub-optimal (0.1 MPa) and supra-optimal (90 MPa) conditions), no classical stress response was observed. Instead, we observed an unexpected transcriptional modulation of more than a hundred gene clusters, under the putative control of the master transcriptional regulator SurR, some of which are described as being involved in energy metabolism. This suggests a fine-tuning effect of HHP on the SurR regulon. Pressure could act on gene regulation, in addition to modulating their expression.